Snakes, Sharks, and the Great Barrier Reef: Selected Use of Anglicisms to Represent Australia in the Australian German-Language Newspaper, Die Woche - Hunt, Jaime W. (Frontiers in Communication, 2022)
Much research into language contact, specifically on anglicisms in German, investigates the appearance and use of English borrowings in the print media published in Germany, Austria, or Switzerland. While these publications are intended for a German-speaking audience in majority German-speaking countries, it remains to be explored what happens to English loans when they appear in a German-language publication produced in a majority English-speaking country. This raises questions about how the local environment, issues and events related to the country of publication are represented lexically to a local audience who are familiar with these concepts in English. Using both quantitative and qualitative methods, I analyze a selection of anglicisms related to Australia in a corpus of 25,147 types and 223,671 tokens from the Australian-published German-language newspaper Die Woche. The findings indicate that most of these anglicism types occur within the semantic fields of place and society. The frequency and distribution of various types, such as adapted and unadapted borrowings, loan translations and loan renditions, including flagged lexical units and codeswitching, appears to be determined mostly by authorship and intended audience of individual articles rather than the newspaper as a whole. Articles attributed to the dpa (Deutsche Presse-Agentur ‘German Press Agency’) contain a higher incidence of loan translations, loan renditions, and flagging devices, particularly of proper nouns, than those attributed to local journalists. While this may allow international readers of the articles distributed via the dpa to better understand Australian events, institutions, social phenomena, and place, it may have a distancing or even alienating effect for local German-speakers, situating them outside mainstream Australian society.